Adaptive optics enhanced direct laser writing of high refractive index gyroid photonic crystals in chalcogenide glass - Cumming, Benjamin P.; Turner, Mark D.; Schröder-Turk, Gerd; Debbarma, Sukanta; Luther-Davies, Barry; Gu, Min (Optics Express, 2014)
Chiral gyroid photonic crystals are fabricated in the high refractive index chalcogenide glass arsenic trisulfide with an adaptive optics enhanced direct laser writing system. The severe spherical aberration imparted when focusing into the arsenic trisulfide is mitigated with a defocus decoupled aberration compensation technique that reduces the level of aberration that must be compensated by over an order of magnitude. The fabricated gyroids are shown to have excellent uniformity after our adaptive optics method is employed, and the transmission spectra of the gyroids are shown to have good agreement with numerical simulations that are based on a uniform and diffraction limited fabrication resolution.
EAM Import::2019-03-13